Analisis Faktor Kepuasan Pelanggan Service Mobil Pada Bengkel Daihatsu Cabang Maumere - Anastasia Aprilianti Jaja Wain (Jurnal Medika Nusantara, 2023)
Customer satisfaction or dissatisfaction is the key to success in a company. The higher the level of customer satisfaction, the greater the profit for the company, because this will have an impact on the desire of customers to return to using the products and services provided. This study has two objectives, first, to determine the factors that influence customer satisfaction of car service at Daihatsu workshop, Maumere branch, and second, to determine the most dominant factor influencing customer satisfaction using service at the Daihatsu workshop, Maumere branch. The sample of this study consisted of 50 respondents from customers who used car service at the Daihatsu workshop, Maumere branch with the following criteria: a). Using the Daihatsu car brand and other car brands. b). Using the Daihatsu car repair shop service more than twice. The sampling technique uses incidental sampling. The scale used in this study is a scale of service quality, brand image or company image, and prices compiled by the researchers themselves. The service quality scale has a reliability coefficient of 0.899, the brand image scale has a reliability coefficient of 0. 800, and the price scale has a reliability coefficient of 0.894. This research includes quantitative research with an exploratory factor analysis approach. The results of this study indicate that service quality, brand image or company image and price are factors that affect customer satisfaction of car service at the Daihatsu Maumere branch, which can be explained by the results of the factor analysis test which shows that the KMO, Bartlett’s Test, and MSA numbers have met. criteria or terms in the factor analysis provisions: The number of KMO is 0.556 with the Bartlett’s Test 0.000. MSA numbers are: service quality factor gives MSA number of 0.529, brand image factor gives MSA number of 0.674 and price factor gives MSA figure of 0.533.